Development and Validation of New Analytical Method for The Simultaneous Estimation of Darunavir And Ritonavir in Pharmaceutical Dosage Form - Pemra Raju; K. Thejomoorthy; P.Sreenivasa Prasanna (International Journal of Indigenous Herbs and Drugs, 2021)
A simple, Accurate, precise method was developed for the simultaneous estimation of the Darunavir and Ritonavir in Tablet dosage form. The chromatogram was run through Agilent C18 150 x 4.6 mm, 5m. Mobile phase containing Buffer 0.1% Formic acid: Acetonitrile, taken in the ratio 70:30 was pumped through the column at a flow rate of 0.95 ml/min. The temperature was maintained at 30°C. The optimized wavelength selected was 293 nm. The retention times of Darunavir and Ritonavir were found to be 2.369min and 2.911. %RSD of the Darunavir and Ritonavir were and found to be 0.7 and 0.5 respectively. %Recovery was obtained as 99.67% and 99.78% for Darunavir and Ritonavir respectively. LOD, LOQ values obtained from regression equations of Darunavir and Ritonavir were 1.49, 5.191and 0.37, 1.11 respectively. Regression equation of Darunavir is y = 5421x + 640.7, and y = 3870.x + 5191 of Ritonavir. Retention times were decreased and run time was decreased, so the method developed was simple and economical that can be adopted in regular Quality control tests in Industries.